-4(2x-3) + 4x = 9x -4x +8 -4 answer this

Question

-4(2x-3) + 4x = 9x -4x +8 -4 answer this

in progress 0
Kiệt Gia 2 months 2021-07-25T17:12:48+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-07-25T17:14:26+00:00

    Answer:

    x = 8/9

    Step-by-step explanation:

    -4(2x-3) + 4x = 9x -4x +8 -4  

    2x*(-4) -3*(-4) + 4x = 9x – 4x  + 8 – 4

    -8x + 12 + 4x = 9x – 4x + 8 – 4         {Combine like terms}

    -4x + 12 = 5x + 4

    12  = 5x + 4x + 4

    12 = 9x + 4

    12- 4 = 9x

    9x = 8

    x = 8/9

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )